1997
DOI: 10.1002/(sici)1097-0231(199708)11:12<1279::aid-rcm18>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Rapid separation and characterization of protein and peptide mixtures using 1.5 μm diameter non-porous silica in packed capillary liquid chromatography/mass spectrometry

Abstract: Octadecyl-modified 1.5 µm diameter non-porous silica particles were packed in 150 µm i.d. (360 µm o.d.) capillaries with lengths of 20 cm which were used to separate proteins and peptides generated from enzymatic digests of proteins. Gradients were produced using an exponential dilution method at pressures of 520 Bar (7500 psi) and electrospray ionization mass spectrometry was used for detection. This system was similar to packed capillary perfusion chromatography with respect to chromatographic resolution and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…The electrostatic potential at any point near the surface is related to the net number of electrical charges per unit volume p in the vicinity of the point by the Poisson's equation (2). Far away from the wall, the concentrations of positive and negative ions are equal.…”
Section: Comparison Of the Experimental Data With The Electrokinetic mentioning
confidence: 99%
“…The electrostatic potential at any point near the surface is related to the net number of electrical charges per unit volume p in the vicinity of the point by the Poisson's equation (2). Far away from the wall, the concentrations of positive and negative ions are equal.…”
Section: Comparison Of the Experimental Data With The Electrokinetic mentioning
confidence: 99%
“…To achieve comparable or improved resolution with shorter analysis times, RP columns with smaller particle size must be used in combination with an HPLC system capable of handling very high pressure. MacNair et al have shown that such a system can be constructed and demonstrated its use for the high efficiency separation of small molecules and protein digests (MacNair, Lewis, & Jorgenson, 1997a;MacNair et al, 1997b;MacNair, Patel, & Jorgenson, 1999). Tolley, Jorgenson, and Moseley, 2001 have demonstrated that high quality MS/MS spectra can be obtained for protein digests analyzed using a hybrid qTOF mass spectrometer coupled to an ultra high performance HPLC (UPLC) with a column packed with 1.5 mm sized particles.…”
Section: A Ultra High Performance Liquid Chromatographymentioning
confidence: 99%
“…The use of small spheres (1.5–3 μm) significantly enhances the separation efficiency15 under the limitation, however, of a drastically increased column back‐pressure 16. The capillaries packed with these particles (either porous or non‐porous) are capable of providing high separation efficiency in reasonably short elution times only if they are operated as very short beds or with expensive ultra‐high pressure LC equipment enabling system pressure drops between 700 and 1100 bar 17–19…”
Section: Characteristic Physical Properties Of the Different Capillarmentioning
confidence: 99%